Abderrahman Beggar. Histoire et mémoire bouraouïennes - Sasu, Voichita-Maria (Revue CMC Review, 2017)
Voichita-Maria Sasu’s long review article offers a perceptive analysis of Abderrahman Beggar’s study of Hédi Bouraoui’s work, Histoire et mémoire bouraouïennes I. She notes that Beggar presents a theoretical critique focusing on these two major themes which examines not only literature and history, but also philosophy, art, and politics, in a comparative framework.